Analisis Pengaruh Lokasi, Variasi Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian pada Toko Sihab Grosir dan Eceran di Kecamatan Padaherang - Halda Nurohmah; Muchammad Agung Miftahudin; Arini Hidayah; Meydy Fauziridwan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The growth of the retail industry in Padaherang District, Pangandaran Regency, has intensified competition between modern retail outlets and traditional stores, including staple goods businesses. This study aims to analyze the influence of location, product variety, and service quality on consumer purchasing decisions at Toko Sihab (Wholesale and Retail). A quantitative approach was employed using a survey method involving 110 respondents drawn from an estimated population of 1,500 customers, determined based on Roscoe’s guideline. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that, both partially and simultaneously, location, product variety, and service quality have a positive and significant effect on consumer purchasing decisions. A strategic and accessible location, a wide variety of products that meet consumer needs, and friendly, responsive service are key factors in attracting and retaining customers. These findings highlight the importance of consumer-oriented marketing strategies in enhancing the competitiveness of traditional retail stores amid the growing dominance of modern retail outlets.